Bites : seven courses, one meal : star soup, hog roast, cold cuts, (pickle), ice cream, jelly, and hundreds and thousands /: seven courses, one meal : star soup, hog roast, cold cuts, (pickle), ice cream, jelly, and hundreds and thousands. (2005) - Unknown
No abstract available